Exploring nuclear structure with multiparticle azimuthal correlations at the LHC - Acharya, S.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (Elsevier, 2025)
Details of the nuclear structure of 129Xe, such as the quadrupole deformation and the nuclear diffuseness, are studied by extensive measurements of anisotropic-flow-related observables in Xe–Xe collisions at a centre-of-mass energy per nucleon pair √𝑠 NN = 5.44 TeV with the ALICE detector at the LHC. The results are compared with those from Pb–Pb collisions at √𝑠 NN = 5.02 TeV for a baseline, given that the 208Pb nucleus exhibits a very weak deformation. Furthermore, comprehensive comparisons are performed with a state-of-the-art hybrid model using IP-Glasma+MUSIC+UrQMD. It is found that among various IP-Glasma+MUSIC+UrQMD calculations with different values of nuclear parameters, the one using a nuclear diffuseness parameter of 𝑎0 = 0.492 and a nuclear quadrupole deformation parameter of 𝛽2 = 0.207 provides a better description of the presented flow measurements. These studies represent the first systematic exploration of nuclear structure at TeV energies, utilizing a comprehensive set of anisotropic flow observables. The measurements serve as a critical experimental ben
Keywords: Physics; Large Hadron Collider; Nuclear physics; Particle physics; Azimuth; Astronomy; https://purl.org/pe-repo/ocde/ford#1.03.04